Camera-Sourced Heart Rate Synchronicity: A Measure of Immersion in Audiovisual Experiences - Joseph Williams; Jon Francombe; Damian Murphy (Applied Sciences, 2024)
Audio presentation is often attributed as being capable of influencing a viewer’s feeling of immersion during an audiovisual experience. However, there is limited empirical research supporting this claim. This study aimed to explore this effect by presenting a clip renowned for its immersive soundtrack to two groups of participants with either high-end or basic audio presentation. To measure immersion, a novel method is applied, which utilises a camera instead of an electroencephalogram (ECG) for acquiring a heart rate synchronisation feature. The results of the study showed no difference in the feature, or in the responses to an established immersion questionnaire, between the two groups of participants. However, the camera-sourced HR synchronicity feature correlated with the results of the immersion questionnaire. Moreover, the camera-sourced HR synchronicity feature was found to correlate with an equivalent feature sourced from synchronously recorded ECG data. Hence, this shows the viability of using a camera instead of an ECG sensor to quantify heart rate synchronisation but suggests that audio presentation alone is not capable of eliciting a measurable difference in the feeling of immersion in this context.